The C in ORCID: from authorship to contributorship - Mejias, Gabriela; Marín-Arraiza, Paloma (Septentrio Conference Series, 2020)
See RECORDING. ORCID is part of the wider digital infrastructure needed for all those who participate in research, scholarship and innovation to share information on a global scale. As part of our commitment with openness, we enable transparent and trustworthy connections between researchers, their contributions, and activities by providing an identifier for individuals to use with their name as they engage in research. Since its foundation in 2013, ORCID has aimed to enable and improve recognition for a broader range of contributions than textual publications. Its current worktype list includes 43 different types of contributions. In combination with acknowledging further contributions, ORCID also considers research resources (infrastructure, collection, equipment and service) to provide a better understanding of the impact of the work undertaken by researchers using them. This webinar will explore how ORCID supports the creation of a permanent, and unambiguous record of research and scholarly communication by enabling reliable attribution of contributors and their activities. The session will focus on the development and current implementation of ORCID tools to acknowledge and encourage contributions such as preprints and peer review activities, as well as the work being done to support contributor roles (CRediT taxonomy). The session will also showcase an analysis of the current community adoption of these features and aims to trigger a discussion on the future of the scholarly record.